Editors' Choice—Review—Nanostructured Electrodes as Random Arrays of Active Sites: Modeling and Theoretical Characterization. Issue 1 (1st January 2020) - Oleinick, Alexander; Sliusarenko, Oleksii; Svir, Irina; Amatore, Christian
Abstract : This review presents the main principles underlying the theoretical description of the behavior of regular and random arrays of nanometric active sites. It is further shown how they can be applied for establishing a useful semi-analytical approximation of the arrays responses under diffusion limited conditions when they involve the common situation of active sites with identical sizes. This approximation is general and, as exemplified for different type of arrays, can be employed for describing the behavior of any array involving arbitrary distributions of their active sites onto the substrate surface. Furthermore, this efficient approach allows statistical characterization of active sites distributions of any array based on chronoamperometric data.